Decomposition of both Eragrostis plana biomass and soil influences the phytotoxicity and chemical characteristics of extracts - Bittencourt, Henrique von Hertwig (2018)
Eragrostis plana is an exotic and resilient weed in southern South America rangeland and pastureland. The goal of this study was to determine the phytotoxicity and chemical characteristics of extracts obtained from E. plana shoot residue. Bioassays evaluating the phytotoxicity of the extracts on the development of Triticum aestivum seedlings were completely randomized and consisted of four replicates in a two-factorial scheme. The levels of factor A consisted of shoot biomass, biomass + soil, and soil material, whereas the levels of factor B consisted of the incubation periods of 1, 3, 7, 10, 14, and 21 days. The radicle length of T. aestivum seedlings was reduced by biomass and biomass + soil after 1 and 10 days and after 1, 3, 10, and 14 days of incubation, respectively. The hypocotyl length was reduced by the biomass and biomass + soil extracts after 10 and 14 days and after 1, 3, 10, 14, and 21 days of incubation, respectively. The soil extracts allowed longer T. aestivum radicles and hypocotyls than did the control. The pH values did not differ between biomass, biomass + soil, and soil, whereas the highest electrical conductivity values were registered for the biomass extracts, followed by the biomass + soil and soil extracts, with the last showing extremely low levels. The total phenolic concentrations in all decomposed materials were higher during the first few days but gradually decreased with increasing incubation period. The combination of biomass and soil increased the phytotoxicity of the biomass, necessitating additional studies on the interaction between the allelochemicals produced by these plants and the soil.